Effectiveness of Xenon as a Fire Suppressant Under Microgravity Combustion Environment. Issue 2 (1st February 2016) - Alam, Fahd E.; Dryer, Frederick L.; Farouk, Tanvir I.
ABSTRACT: The 'FLame EXtinguishment' (FLEX) program conducted by NASA on board the International Space Station (ISS) has been assisting in developing fire-safety protocols for low gravity applications through microgravity droplet combustion experiments. A wide range of fuels, including alcohols and alkanes, have been studied in different ambient conditions that also encompass the use of various diluent species and concentrations. A prime focus of the work has been to observe the relative effectiveness of atmospheric composition and pressure changes on fire suppression under 'reduced' gravity conditions. Here, detailed numerical simulations are performed to investigate the combustion and extinction characteristics of isolated sphero-symmetric 1.0–2.0-mm diameter methanol droplets burning in xenon (Xe)-enriched environments. Comparisons of diluent behaviors under identical conditions using argon (Ar), carbon dioxide (CO2 ), and helium (He) as the alternative diluent to nitrogen are also reported. The predictions are compared against ISS experiments with good agreement and with less satisfactory agreement with the results published earlier by Shaw and Wei (2012). Xenon as diluent rather than nitrogen results in reduced burning rate, larger extinction diameter and counter intuitively, and prolonged burning time. The limiting oxygen index (LOI) for xenon is found to decrease significantly from that found with argon, carbon dioxide, or helium. The numerical analyses indicate that the lower thermal diffusivity of xenon is the principal factor responsible for the remarkably lower LOI. Water accumulation within the methanol droplet and its relevance to the extinction process is also discussed. It is concluded that the combined observation of elevated peak gas temperature, its slow decay due to minimal diffusive heat loss, and the exceptionally lower LOI value associated with xenon as a diluent all detract from its utility for suppressing fire concerns in reduced gravity applications.